Pengaruh Biaya Overhead Pabrik (BOP) dan Biaya Tenaga Kerja Langsung terhadap Harga Pokok Produksi di PT.Azmindo Baja Cakrabuana - medianty, sofi (COMPETITIVE, 2023)
This research was motivated by the cost of goods manufactured which experienced ups and downs, the problem in this study was whether factory overhead costs and direct labor costs had a partial or simultaneous positiveeffect on PT.Azmindo Baja Cakrabuana.This study aims to determine the effect of factory overhead costs and direct labor costs on the cost of production. The method used in this study is the quantitative method, the result show that partially positive effect between the variable factory overhead costs (X1) on the costs of goods manufactured (Y) with t-count value of 2,023 and also t-tabel of 60 data, which is 2,002 which it means that the t count is greater that the t table (2,023 > 2,002), then the significant value obtained is 0,048 < 0,05.  And also has a positive effect on the direct labor costs variable (X2) on the costs of goods manufactured (Y) with t-count value of 2,432 and a t-table value of data 60 which is 2,002 , which means that t-count is greater than t-table (2,432 > 2,002) and also obtained a significant value of 0,018 < 0,05. There is also a simultaneous posistive effect on the variabel factory overhead costs (X1) and direct labor costs (X2) on the variable cost of goods manufactured (Y) simultaneously with the calculated F value and F table of 6,095 and the F table value of 3,159 , the calculated F value is more greater than the F table value (6,095 > 3, 159) with a significant level of 0,004 < 0,05.  Keywords : Factory overhead costs, Direct labor costs, Cost of goods manufactured